Trends of the Intra‐Annual Onset and End of Humid Heatwaves in the Northern Hemisphere - Jianquan Dong; Stefan Brönnimann; Tao Hu; Xueyan Cheng; Yanxu Liu; Jian Peng (Earth's Future)
Abstract Humid heatwaves negatively affect human health due to the integrating effect of temperature and humidity, and thus the early warning and timely mitigating on climate extremes are essential. Yet, systematic assessment on the intra‐annual onset and end of humid heatwaves, which is associated to the occurrence of first and last humid heatwaves, are missing globally. Using a new station‐based data set of daily maximum wet‐bulb temperature, the start and end dates, cumulative anomaly and extremely humid heat of the first and last humid heatwaves in the Northern Hemisphere were explored. It was found that at 91.54% of stations, humid heatwaves started earlier or ended later in the period of 2001–2020 compared to 1981–2000. High cumulative anomalies of the first or last humid heatwaves were found in the mid‐ and high‐latitude regions. Average difference between all humid heatwaves and the first humid heatwaves in cumulative anomalies increased steadily at stations north of 35°N. At regional scales, South East Asia had become the most prominent area with intensification of intra‐annual onset and end of humid heatwaves and will experience more frequent extreme events by 2100. Our findings demonstrated more intensified characteristics of the intra‐annual onset and end of humid heatwaves, calling for global awareness.